2014
DOI: 10.1007/s00122-014-2448-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi-environment multi-QTL association mapping identifies disease resistance QTL in barley germplasm from Latin America

Abstract: Multi-environment multi-QTL mixed models were used in a GWAS context to identify QTL for disease resistance. The use of mega-environments aided the interpretation of environment-specific and general QTL. Diseases represent a major constraint for barley (Hordeum vulgare L.) production in Latin America. Spot blotch (caused by Cochliobolus sativus), stripe rust (caused by Puccinia striiformis f.sp. hordei) and leaf rust (caused by Puccinia hordei) are three of the most important diseases that affect the crop in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 84 publications
4
45
0
2
Order By: Relevance
“…Genotype ´ environment interaction has been exploited in genomic studies to map quantitative trait loci in balanced populations (Piepho, 2000;Malosetti et al, 2004;van Eeuwijk et al, 2005;Boer et al, 2007;Mathews et al, 2008) and genome-wide association studies (Gutiérrez et al, 2015) using mixed models. Additionally, GS studies have included GEI information by performing overall predictions across environments (Heffner et al, 2011;Resende et al, 2011), within environments or groups of environments (Burgueño et al, 2012;Ly et al, 2013;Dawson et al, 2013;Heslot et al, 2014), or using marker-by-environment predictions (Jarquín et al, 2014;Lopez-Cruz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Genotype ´ environment interaction has been exploited in genomic studies to map quantitative trait loci in balanced populations (Piepho, 2000;Malosetti et al, 2004;van Eeuwijk et al, 2005;Boer et al, 2007;Mathews et al, 2008) and genome-wide association studies (Gutiérrez et al, 2015) using mixed models. Additionally, GS studies have included GEI information by performing overall predictions across environments (Heffner et al, 2011;Resende et al, 2011), within environments or groups of environments (Burgueño et al, 2012;Ly et al, 2013;Dawson et al, 2013;Heslot et al, 2014), or using marker-by-environment predictions (Jarquín et al, 2014;Lopez-Cruz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches have been proposed to study GEI such as linear-bilinear models (Finlay and Wilkinson, 1963;Gauch, 1992;Yan et al, 2001;Crossa and Cornelius, 2002), mixed models (Piepho, 1998;Burgueño et al, 2008;Cullis et al, 2010), and crop growth models (Chapman, 2008;Technow et al, 2015;Malosetti et al, 2016). These methods have been extensively used for different breeding strategies including traditional phenotypic selection and testing (Yan et al, 2007;González-Barrios et al, 2017), quantitative trait loci mapping (Piepho, 2000;Malosetti et al, 2004;Mathews et al, 2008;Quero et al, 2014), genome-wide association mapping (van Eeuwijk et al, 2010;Locatelli et al, 2013;Gutiérrez et al, 2015;Racedo et al, 2016;Monteverde et al, 2018), and genomic selection (Burgueño et al, 2012;Lopez-Cruz et al, 2015;Lado et al, 2016). Environments can then be grouped in sets that produce a similar ranking of the genotypes (mega-environments [MEs]; Braun et al, 1996).…”
mentioning
confidence: 99%
“…However, both approaches seem to be complementary in the sense that their ultimate goal is the detection of the genes underlying the quantitative complex trait for further cloning. Several examples of the use of the association mapping approach in QDR studies for the more limiting diseases can be found in recent literature (Benson et al, 2015;Gutiérrez et al, 2015;Arruda et al, 2016;Iquira et al, 2015;Olukolu et al, 2016;Turuspekov et al, 2016). However, despite the broad use of this approach, no genes detected by AM for plant QDR have been cloned so far.…”
Section: How To Study Complex Traits and Qdrsmentioning
confidence: 99%